Wrist and hand pain in orthopaedic physical therapists: A mixed-methods study. (October 2019) - Campo, Marc; Hyland, Matthew; Sueki, Derrick; Pappas, Evangelos
Abstract: Background: Orthopaedic physical therapists (PTs) who perform manual therapy are at high risk for wrist and hand pain. Studies that examine the magnitude, scope and causes of wrist and hand pain are needed so that prevention programs can be developed. Objectives: The objective of this study was to determine the magnitude, scope, and impact of wrist and hand pain in orthopaedic PTs and to identify potential strategies for prevention. Design: This was a sequential, mixed methods study including quantitative and qualitative components. Methods: The quantitative phase consisted of an online survey sent to members of the Academy of Orthopaedic Physical Therapy. The qualitative phase consisted of focus groups with Orthopaedic PTs who had wrist and hand pain. Results: The survey included 962 PTs and the focus groups included 10 PTs. The one-year prevalence of wrist and hand pain was 75%. Increasing age, decreasing experience, female gender, performing more manual therapy and working more than 40 h per week were associated with an increased risk of moderate to severe wrist and hand pain. Soft-tissue mobilization was the most frequently cited causative factor. The most commonly mentioned strategy for prevention was altering body mechanics and technique. Focus group participants highlighted the importance of managing expectations for manual therapy by patients. Conclusions: Formal injury prevention programs for PT students and PTs are urgently needed. These programs should focus on improving body mechanics and technique, attention to workload, careful selection of manual techniques, and managing expectations for manual therapy. Highlights: The one-year prevalence of wrist and hand pain in orthopaedic PTs was 75%. Soft-tissue mobilization was the most frequently cited risk factor. Preventive strategies included body mechanics and performing less manual therapy. Managing patient expectations for manual therapy was a challenge for PTs.